Leisure time computer use and adolescent bone health—findings from the Tromsø Study, Fit Futures: a cross-sectional study. Issue 6 (22nd April 2015) - Winther, Anne; Ahmed, Luai Awad; Furberg, Anne-Sofie; Grimnes, Guri; Jorde, Rolf; Nilsen, Ole Andreas; Dennison, Elaine; Emaus, Nina
Abstract : Objectives: Low levels of physical activity may have considerable negative effects on bone health in adolescence, and increasing screen time in place of sporting activity during growth is worrying. This study explored the associations between self-reported screen time at weekends and bone mineral density (BMD). Design: In 2010/2011, 1038 (93%) of the region's first-year upper-secondary school students (15–18 years) attended the Tromsø Study, Fit Futures 1 (FF1). A follow-up survey (FF2) took place in 2012/2013. BMD at total hip, femoral neck and total body was measured as g/cm² by dual X-ray absorptiometry (GE Lunar prodigy). Lifestyle variables were self-reported, including questions on hours per day spent in front of television/computer during weekends and hours spent on leisure time physical activities. Complete data sets for 388/312 girls and 359/231 boys at FF1/FF2, respectively, were used in analyses. Sex stratified multiple regression analyses were performed. Results: Many adolescents balanced 2–4 h screen time with moderate or high physical activity levels. Screen time was positively related to body mass index (BMI) in boys (p=0.002), who spent more time in front of the computer than girls did (p<0.001). In boys, screen time was adversely associated with BMDFF1 at all sites, and these associations remained robust to adjustments for age, puberty, height, BMI, physical activity, vitamin D levels, smoking, alcohol, calcium and carbonated drink consumption (p<0.05). Screen time was also negatively associated with total hip BMDFF2 (p=0.031). In contrast, girls who spent 4–6 h in front of the computer had higher BMD than the reference (<2 h). Conclusions: In Norwegian boys, time spent on screen-based sedentary activity was negatively associated with BMD levels; this relationship persisted 2 years later. Such negative associations were not present among girls. Whether this surprising result is explained by biological differences remains unclear.